Analysis of mercury concentrations in groundwater: an Applied study using data from the United States Geological Survey (The International Journal for Scientific Research, 2025)
This study aims to analyze mercury concentrations in groundwater using the U.S. Geological Survey's National Water Information System (NWIS) database. The study included an analysis of 2,252 samples from 15 U.S. states over the period 1970–2024, using a combination of statistical and spatial analyses to assess the geographic and temporal distribution of mercury concentrations and compare them to environmental standards. The results showed that the average mercury concentration in the studied samples was 5.0024 micrograms/litter, which is higher than the Environmental Protection Agency standard for drinking water (2 micrograms/litter), while the median value was 0.1000 micrograms/litter, this indicates the presence of extreme values that affected the overall average. The study revealed significant variation in mercury concentrations between different states, with Colorado recording the highest average (57.95 µg/L), followed by New York (20.41 µg/L) and New Jersey (4.83 µg/L). New Jersey also recorded the highest percentage of exceedances of the EPA standard (14.84%), followed by Mississippi and Nebraska (10% each). Time trend analysis showed an overall decrease in mercury concentrations over the studied period (p=0.0004), reflecting the effectiveness of regulatory and control measures to reduce mercury pollution. Spatial variation in mercury concentrations can be explained by several factors, including historical mining and industrial activities and natural geological formations. The study emphasizes the importance of adopting an integrated approach to managing groundwater mercury contamination, including intensifying monitoring programs in high-risk areas, identifying and assessing pollution sources, developing effective treatment technologies, and regulating the use of groundwater for irrigation, particularly in contaminated areas, to mitigate its health and environmental impacts.
Keywords: Mercury; Groundwater; Water Pollution; USGS; Spatial Analysis; Geographic Distribution; Temporal Trends